2013
DOI: 10.1212/wnl.0b013e31827b90a8
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy for solitary cysticercus granuloma

Abstract: Objective: The effectiveness of anthelminthic and corticosteroid drug therapy in parenchymal neurocysticercosis is well established. The treatment of parenchymal solitary cysticercus granuloma (SCG), however, remains controversial. We attempted to obtain a consistent estimate of the efficacy of anthelminthic and corticosteroid drug treatment in SCG.Methods: Randomized-controlled trials (RCTs) comparing rates of seizure freedom, granuloma resolution, and residual calcification in individuals with SCG treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 35 publications
2
43
0
9
Order By: Relevance
“…Although these calcifications cannot usually be differentiated from similar calcified lesions due to other etiologies, there is little question that most are derived from degenerating granulomas. The most direct evidence comes from serial observations using computerized tomography (CT) and magnetic resonance imaging (MRI) of patients with characteristic T. solium cysts that degenerate naturally or following cysticidal treatment [20, 21]. In a sizable proportion, these lesions gradually become calcified, typically evolving into characteristic dense calcifications.…”
Section: Characteristics Of Calcified Neurocysticercosismentioning
confidence: 99%
“…Although these calcifications cannot usually be differentiated from similar calcified lesions due to other etiologies, there is little question that most are derived from degenerating granulomas. The most direct evidence comes from serial observations using computerized tomography (CT) and magnetic resonance imaging (MRI) of patients with characteristic T. solium cysts that degenerate naturally or following cysticidal treatment [20, 21]. In a sizable proportion, these lesions gradually become calcified, typically evolving into characteristic dense calcifications.…”
Section: Characteristics Of Calcified Neurocysticercosismentioning
confidence: 99%
“…5 Antiparasitic treatment of patients with viable intraparenchymal brain cysts seems to improve the prognosis of their seizure disorders. 69 However, antiparasitic treatment has suboptimum efficacy, killing roughly 65% of parasites and obtaining complete cyst resolution (no viable parasites remaining) in less than 40% of patients after a course of praziquantel or albendazole. 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Calcification in NCC is a common long-term outcome with observed rates of calcification in pediatric NCC varying widely from 6.2% to as high as 60% [24]. Interestingly, cysticidal therapy was found to have no significant effect in the calcification of solitary parenchymal NCC [25, 26]. A retrospective analysis of solitary parenchymal NCC from India [24] reported that the risk of breakthrough seizures was significantly higher in calcified lesions on follow-up scan when compared to normal scans or persisting lesions.…”
Section: Discussionmentioning
confidence: 99%